Reflections on Strategies for Catholic Studies. - Wright, Allan F. (Logos: A Journal of Catholic Thought & Culture)
The article focuses on integrating the element of witness into Catholic Studies education, emphasizing the need for personal faith experiences and active spirituality in students' lives. Topics discussed include the challenge of disconnect between religious beliefs and real-world experiences, the importance of witness in conveying faith, and strategies for incorporating spirituality into various academic disciplines.